Risk factors for the occurrence of epistaxis: Prospective study. Issue 3 (June 2018) - Côrte, Filipa Camacho; Orfao, Tiago; Dias, Cláudia Camila; Moura, Carla Pinto; Santos, Margarida
Abstract: Objective: Analyse and compare the characteristics of patients with epistaxis admitted to the otolaryngology emergency department with those provided by a control group. Establish a model to identify epistaxis predictive factors. Methods: Prospective analysis of 283 consecutive adults, admitted to the otolaryngology emergency department of a tertiary referral centre between 25 January and 25 February 2014. Comparison of gender, age, co-morbidities, usual medication, history of epistaxis or nasal trauma, presence of septal deviation and blood pressure value on admission, between the elements that were admitted to the emergency due to epistaxis (group 1) and a group composed of patients with other symptoms (group 2). Intergroup variations were analyzed using t student and chi-square tests. Multivariate logistic regression and a receiver operating characteristic curve were used to establish a predictive model and test its suitability. Results: Male gender (OR = 2.57, 95% CI 1.1–6.0, p = 0.029), older age (OR = 1.03, 95% CI 1.0–1.1, p = 0.002), existence of peripheral vascular disease (OR = 13.47, 95% CI 1.9–95.3, p = 0.009), cardiovascular disease (OR = 3.91, 95% CI 1.6–9.7, p = 0.003) and previous history of epistaxis (OR = 5.53, 95% CI 2.5–12.1, p < 0.001) were predictors of epistaxis when adjusted for the presence of elevated blood pressure, history of hypertension, cerebrovascular disease and chronic use of anticoagulants or antiplatelet drugs. The model revealed a good applicability (area under the curve of 0.852). Conclusions: The only predictive factors of admission to the emergency department due to epistaxis were male gender, older age, peripheral vascular disease, cardiovascular disease and history of epistaxis.